The TESOL Encyclopedia of English Language Teaching 2018
DOI: 10.1002/9781118784235.eelt0207
|View full text |Cite
|
Sign up to set email alerts
|

Planning and Class Management

Abstract: Planning is a process of determining what to teach and how to teach it. This process involves formulating specific objectives, procedures, techniques, activities and evaluation methods to check to what extent the expected learning outcomes have been accomplished. The format of a lesson plan may differ from one teacher to another or from one school to another. Planning lessons may not be effective without proper classroom management of the available resources, procedures, and class time as well as the physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This study aimed to analyse the correlations between teachers' classroom management skills, confidence in teachers and students' perceptions of educational stress on the basis of views stated by 608 secondary school students. Previous studies indicated that teachers with developed classroom skills affected students' behaviours in positive ways (Emmer & Emertson, 2013;Fareh, 2018;Raider-Roth, 2005;Walker, Ramsey, & Gresham, 2004). It was also found by studies that students' confidence in teachers improved teacher-student relations.…”
Section: Discussion Results and Recommendationsmentioning
confidence: 91%
See 2 more Smart Citations
“…This study aimed to analyse the correlations between teachers' classroom management skills, confidence in teachers and students' perceptions of educational stress on the basis of views stated by 608 secondary school students. Previous studies indicated that teachers with developed classroom skills affected students' behaviours in positive ways (Emmer & Emertson, 2013;Fareh, 2018;Raider-Roth, 2005;Walker, Ramsey, & Gresham, 2004). It was also found by studies that students' confidence in teachers improved teacher-student relations.…”
Section: Discussion Results and Recommendationsmentioning
confidence: 91%
“…According to another definition, classroom management is the system of educating which regulates the physical environment of the classroom and which affects students' behaviours so as to facilitate learning (Bean, 2007). Fareh (2018) argues that effective classroom management creates an environment appropriate for learning and thus plays an indispensable role in encouraging learning. There are studies supporting the idea that students display disruptive and maladaptive behaviours in circumstances where classroom management is weak (Little E. & Hudson, 1998;Oliver, Wehby, & Reschly, 2011).…”
Section: Classroom Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it contains clarifying the instructions, fulfilling the purpose and the structure of the lesson, appropriate materials, providing group focus and classroom conditions (Doyle, 2006 ; Kounin, 1970 ). Another significant aspect of classroom management is establishing rules and regulations which can positively affect learners' behavior (Emmer & Emertson, 2013 ; Fareh, 2018 ; Raider-Roth, 2005 ; Walker, Ramsey, & Gresham, 2004 ). In 2004, Jones and Jones published a paper about classroom management in the context of three approaches entail counseling which focuses on maintaining learners under discipline, behaviorist approach which concentrates on modification techniques for learner’s undesirable behaviors, and preventive approach which emphasizes to hinder learners’ misbehaviors.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In the meanwhile, the management of the online courses changed, and new strategies were adopted. Several studies supported that classroom management has correlations with some variables including self-control, responsibility, psychological well-being, and discipline, influencing academic outcomes (Bean, 2007 ; Brophy, 1988 ; Fareh, 2018 ; Jones & Jones, 2004 ; Marzano, Marzano, & Pickering, 2003 ; Savage & Savage, 2009 ; Wang et al, 1993 ). Moreover, evidence suggests that teachers with professional classroom skills impact learners’ behaviors positively (Emmer & Emertson, 2013 ; Fareh, 2018 ; Raider-Roth, 2005 ; Walker, Ramsey, & Gresham, 2004 ).…”
Section: Introductionmentioning
confidence: 99%